STUDY SCANDIUM (SC) METAL ENRICHMENT CHARACTERISTICS IN LATERIT NICKEL DEPOSITS I THE POMALAA REGION, KOLAKA DISTRICT, SOUTHEAST SULAWESI PROVINCE - Setiawan, Erwin
The research location is in IUP OP UBPN Kolaka, PT Antam Tbk, Pomalaa District, Kolaka Regency, Southeast Sulawesi Province. The research area can be reached by air flight from Jakarta to Makassar for about 2 hours, then continued by air flight from Makassar to Kolaka for about 1 hour, then continued by land from Kolaka Airport to the research area for about 45 minutes. The research method used in data collection is to conduct geological mapping, drilling with a total of 52 drill points and sample drill samples of 1253 samples. Evaluation of scandium enrichment in laterite nickel deposits in the research area uses drill core sample data which is then subjected to geochemical analysis using the X-Ray Fluorescence (XRF) method to determine the major element content of 1253 samples and Inductively Coupled Plasma - Optical Emission Spectrometry (ICP-OES) of 1253 samples to determine the scandium content. Petrography of drill core samples was conducted to obtain the rock names of 30 samples while to determine the percentage of constituent minerals, X-Ray Diffraction (XRD) analysis was conducted on 230 samples or 5 drill points. The research area is divided into three prospects, namely the North Block Prospect, the Central Block Prospect and the Maniang Block Prospect. The scandium element is enriched in the limonite zone. Based on physical characteristics, the limonite zone is divided into two types, namely the red limonite zone and the yellow limonite zone. The correlation of scandium elements with oxide compounds using the Spearman correlation method and the classification of the level of relationship between variables refers to Schober, 2018. In the red limonite zone, the scandium element has a weak positive correlation with the Fe2O3 compound with a value of 0.31 and a moderate positive correlation with the Al2O3 compound with a value of 0.51, while entering the yellow limonite zone, the scandium element shows an increase in correlation with the Al2O3 compound which has a strong positive correlation value of 0.80 because altered minerals such as gibbsite and nacrite are formed, then an increase in moderate positive correlation with the Fe2O3 compound which has a value of 0.52 because of the reduction in hematite minerals and the formation of goethite minerals is more dominant. The Cr2O3 compound when entering the yellow limonite zone has a moderate positive correlation pattern with scandium enrichment with a value of 0.53. The type of bedrock has a correlation with scandium enrichment in the study area. In the North Block Prospect, the scandium enrichment levels associated with dunite rocks have an average content of 62.32 ppm and the scandium levels in harzburgite rocks have an average content of 72.43 ppm. In the Central Block Prospect, the scandium enrichment associated with harzburgite rocks has an average content of 72.85 ppm and the scandium levels in lhezorlite rocks have an average content of 64.25 ppm. In the Maniang Block Prospect, the scandium enrichment associated with harzburgite rocks has an average content of 83.22 ppm and the scandium levels in serpentinite rocks have an average content of 79.32 ppm. The harzburgite and serpentinite types of bedrock have relatively higher average scandium levels compared to the scandium enrichment associated with dunite and lhezorlite rocks. The orthopyroxene type of pyroxene mineral is interpreted to carry more scandium compared to the dominant clinopyroxene mineral or the dominant olivine mineral. In the research area, scandium enrichment in the limonite zone has a content ranging from 55 ppm - 127 ppm, then entering the saprolite zone the scandium content will decrease, namely around 11 ppm - 20 ppm and the content will decrease further in the bedrock zone, namely having a scandium content ranging from 5 ppm - 15 ppm.